Efektivitas penggunaan media gambar dalam upaya meningkatkan hasil belajar agama hindu - Ni Luh Kartini (Indonesian Journal of Educational Development, 2020)
This classroom action research aims to determine the increase in learning outcomes of Hinduism through the use of image media. The subjects of this study were grade 1 students of SDN 3 Padangsambian, Denpasar city in the 2020/2021 school year. The object of research is the learning outcomes of Hinduism. Hindu religious learning outcomes data were collected using learning outcome tests. The collected data were analyzed descriptively qualitatively. The criteria for success are as follows: (1) the minimum average daily test score is KKM = 70, and (2) classical learning completeness is at least 85%. The results of preliminary observations made before the action showed that the mean value of Hinduism only reached 67.78 with classical completeness of 61.54%. After the classroom action research was carried out, in the first cycle the average value of the students' daily tests reached 71.84 with 80.77% classical completeness. In the first cycle classical completeness was still below 85% so the cycle was continued to cycle II. After taking the action, in cycle II, the mean score of Hinduism reached 76.19 with classical completeness reaching 88.46%. Thus, the use of image media can improve learning outcomes of Hinduism for grade I SDN 3 Padangsambian students in the 2020/2021 school year in two cycles. Penelitian tindakan kelas ini bertujuan untuk mengetahui peningkatan hasil belajar Agama Hindu melalui penggunaan media gambar. Subjek penelitian ini adalah siswa kelas 1 SDN 3 Padangsambian kota Denpasar tahun pelajaran 2020/2021. Objek penelitian adalah hasil belajar Agama Hindu. Data hasil belajar Agama Hindu dikumpulkan menggunakan tes hasil belajar. Data yang terkumpul dianalisis secara deskriptif kualitatif. Kriteria keberhasilan adalah sebagai berikut: (1) nilai rata-rata ulangan harian minimal sebesar KKM=70, dan (2) ketuntasan belajar klasikal minimal 85%. Hasil observasi awal yang dilakukan sebelum tindakan menunjukkan bahwa nilai rerata Agama Hindu hanya mencapai 67,78 dengan ketuntasan secara klasikal 61,54%. Setelah dilakukan penelitian tindakan kelas, pada siklus I nilai rata-rata ulangan harian siswa mencapai 71,84 dengan ketuntasan klasikal 80,77%. Pada siklus I ketuntasan secara klasikal masih di bawah 85% sehingga siklus dilanjutkan ke siklus II. Setelah dilakukan tindakan, pada siklus II, nilai rerata Agama Hindu mencapai 76,19 dengan ketuntasan klasikal mencapai 88,46%. Dengan demikian, penggunaan media gambar dapat meningkatkan hasil belajar Agama Hindu siswa kelas I SDN 3 Padangsambian tahun pelajaran 2020/2021 dalam dua siklus.